Systematic literature review on the safety and immunogenicity of rotavirus vaccines when co-administered with meningococcal vaccines - Priya Pereira; Bernd Benninghoff; Leentje Moerman (Taylor & Francis Group, 2020)
This study is aimed to review the published evidence on safety, immunogenicity, and efficacy of rotavirus vaccines when co-administered with meningococcal vaccines in infants. A systematic literature search was performed in four databases containing peer-reviewed articles and conference abstracts. In total, twelve articles were included in the review; 11 provided information on safety and five on the immunogenicity of rotavirus vaccines following co-administration. No paper was found on efficacy. Additional routine vaccines were administered in all studies. The safety analysis was mainly focused on fever, vomiting, diarrhea, intussusception, and changes in eating habits. Overall, safety profiles and immune responses associated with rotavirus vaccination were comparable between infants co-administered with rotavirus and meningococcal vaccines and infants receiving rotavirus vaccines without meningococcal vaccines. Although data are limited, co-administration of rotavirus and meningococcal vaccines does not appear to interfere with the safety or immunogenicity of rotavirus vaccines.